Family Support and Psychological Adaptation (Letting-Go) in Primipara Post-partum - Bawafi, Nur Azizah; Nur Rahmawati, Rahajeng Siti; Wijayanti, Lumastri Ajeng (Jurnal Kesehatan, 2024)
During the recovery period, the post-partum mother will experience psychological changes proposed by several theories, which divide the period of psychological adjustment for the post-partum mother through three phases: taking in, taking hold, and letting go. The moms' emotional, intellectual, and behavioral disorders are triggered by their awareness of their guilt. Mothers must adjust to their new positions as they deal with new families with babies. Inadequately adapting to the post-partum period, mothers should get support from the family. This study aimed to determine the relationship between family support and the process of psychological adaptation (letting go) in primiparous post-partum mothers. This study sampled 33 primiparous post-partum mothers using a proportional random sampling technique. These involved primiparous post-partum mothers who lived with their families for 10-42 days and were willing to be respondents. The research used a questionnaire to analyze data. Data analysis using the Kolmogorov-Smirnov showed a p-value of 0.047 (p-valueâ‰¤0.05). The results suggest that there is a relationship between family support and the process of psychological adaptation. Improving early screening for post-partum depression and increasing understanding of mothers and families can help reduce baby blues syndrome and post-partum depression in post-partum mothers.